Additional Chronic Conditions as Barriers to Depression Management Among Adults Living with HIV - Steven A. Lewis; Lynette Phillips; Ann K. Avery (Ohio Journal of Public Health, 2024)
Introduction: An estimated 20% to 30% of people living with HIV (PLHIV) suffer from depression. While the collaborative care model (CCM) is an evidence-based intervention designed to reduce depression, little is known of the impact of additional chronic conditions (ACC) on depression management and CCM response among PLHIV. Methods: A retrospective cohort study was conducted among 412 PLHIV enrolled in CCM at a large urban community hospital in Cuyahoga County, Ohio, between July 1, 2015, and June 30, 3017. Study participants were identified as clinically depressed at enrollment with at least two PHQ-9 measurements within a year of enrollment. Additional chronic conditions were studied to assess their association with depression treatment response or remission during the study period. Multivariable logistic regression was used to model response and remission considering ACC while adjusting for demographic, program-related, and clinical measures. Results: Depression outcomes were no different based on the presence or number of ACC. Study participants age 50 years or over with obesity (aOR: 0.15; 95% CI: 0.04-0.64) or heart disease (aOR: 0.15; 95% CI: 0.03-0.84) were less likely to achieve remission. Participants irrespective of age with musculoskeletal disease (MSD) were less likely to achieve remission compared to others without MSD (aOR: 0.48; 95% CI: 0.25-0.93). Conclusion: Strategies that address obesity may be necessary adjuncts to successfully treating depression among older adults with HIV, while barriers posed by heart disease or MSD should be further investigated.
Keywords: HIV; Depression; Chronic conditions; Obesity; Retrospective cohort study